Modernization of Shakespeare’s Macbeth: A Discourse Analysis - Yasaman Yassipour Tehrani (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Rupert Goold's adaptation of Macbeth (2010) is relatable to some of the dilemmas of the contemporary human beings. In this comparative study, the relationship between the concept of power, images and staging, such as closed and dark spaces, costumes, and scene designs are examined. The present paper draws on Linda Hutcheon’s theory of adaptation and the analysis of the cultural, social and historical context to explain the significance of the film's scene design and spaces. It examines the ways in which new methods are employed to present socio-historical elements in the context of the primary source of the adaptation using Robert Stam’s intertextual dialogism model which helps us to find the relation between images and concepts presented in the film. Goold has attempted to reflect the contemporary situation by using new visual techniques. The paper concludes that similar instances of the exercise of power still exist in the contemporary times. Goold's adaptation is an attempt to make the silenced voices of today’s victims of surveillance and control heard.